(untitled) (American Journal of Business Management, Economics and Banking, 2023)
This study examined the relationship between Human Capital Reporting and Stock Market Performance of Quoted Pharmaceutical Companies in Nigeria for a period of 10 years (2012-2021). Purposive sampling technique was used to collect secondary data for the study from Annual Reports and Accounts of Seven (7) quoted Pharmaceutical companies in the Nigerian Exchange Group (NGX). Ordinary least square and multiple linear regression statistical tools were used to analyze the data with the aid of E-view version 10. The proxies for the independent variable; Human Capital Reporting are; reporting salaries and wages of employees, reporting retirement benefit cost, reporting other employee cost, while market capitalization for the dependent variable Stock Market Performance. The stationarity test shows that the variables are stationary at first difference. The co-integration test proved the presence of a long run relationship. The granger causality test proved no causality between the variables and in testing the hypotheses the independent variables; Reporting salaries and wages of employees, Reporting retirement benefit cost and reporting other employee cost, were statistically significant at 5% level of significance. The study revealed that human capital reporting have positive and statistically significant relationship with the dependent variables; Market capitalization (EPS), The study therefore recommends that adequate reporting and suitable remuneration/ compensation plans should be devised to encourage the acquisition, motivation and retention of valuable, unique, inimitable and well organized human assets who have the greatest potential to drive the performance of pharmaceutical firms in the stock market.